BENEFITS OF WEB-BASED OR ELECTRONIC PORTFOLIO ASSESSMENT IN ESL CLASSROOM - Zulfikar Zulfikar (Universitas Islam Negeri Banda Aceh, 2016)
The effective implementation and use of electronic portfolios in educational institutions confirm their value as an essential teaching and learning instrument. An electronic portfolio is a digital documentation or collection of artifacts (audio/video clips, text, visuals, and coursework) that represent its owner, whether it is an individual, group, or organization. Personal reflection on one’s work, achievement, or thoughts is a key component in many electronic portfolios. Some still question whether electronic portfolios are actually beneficial to the educational process. This piece of work overviews recent literature related to the use of electronic portfolios and examines the issues and challenges of effectively implementing and using electronic portfolios in educational institutions.